PROKALSITONIN SEBAGAI PENANDA PEMBEDA INFEKSI BAKTERI DAN NON BAKTERI - Bastiana Bastiana; Aryati Aryati; Dominicus Husada; M.Y. Probohoesodo (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Early diagnosis of an infection and prompt administration of an antibiotic can dramatically reduce morbidity and mortality.Procalcitonin (PCT), a precursor of calcitonin, has been proposed as a marker of bacterial infection. The aim of this study is to assess theefficiency of procalcitonin in children for the diagnosis of bacterial vs. non bacterial infection. This was a prospective, cross-sectional study.The subjects were enrolled consecutively, consisting of feverish children (temperature ³38.5° C) admitted to the Pediatric EmergencyDepartment with ages up to 12 years old. The subjects were divided into two groups according to their final diagnosis, bacterial and nonbacterial infection. Serum PCT concentration was measured by enzyme linked fluorescent assay (ELFA) method. Sensitivity, specificity,positive predictive and negative predictive values, and receiver operating curve (ROC) of PCT were calculated. Out of 54 patients,24 (44.4%) had a final diagnosis of bacterial infection. PCT showed a wide concentration range in the bacterial infection group (median:1.09 ng/mL, lower (L)=0.05 ng/mL, upper (U)=128.7 ng/mL) compared with non bacterial infection group (0.21 ng/mL; L=0.05ng/mL; U=12.15 ng/mL). There was a significant difference in PCT between the 2 groups (p=0.020). ROC analysis demonstrated anarea under curve (AUC) of 0.686 (95% CI, 0.534 to 0.838). Using a cut-off point of 0.5 ng/mL, the sensitivity, and specificity, positivepredictive and negative predictive values of PCT were 66.7%, 76.7%, 69.6%, 74.2%, respectively. In this study, PCT may be useful fordifferentiation of bacterial vs. non bacterial infection in children.